The virus-induced cytopathic effect - Arias Arias, Jorge Luis (2023)
The cytopathic effect comprises the set of cellular alterations produced by a viral infection. It is of great relevance since it constitutes a direct marker of infection. Likewise, these alterations are often virus-specific which makes them a phenotypic marker for many viral species. All these characteristics have been used to complement the study of the dynamics of virus-cell interactions through the kinetic study of the progression of damage produced by the infection. Various approaches have been used to monitor the cytopathic effect, ranging from light microscopy, immunofluorescence assays, and direct labeling with fluorescent dyes, to plaque assay for the characterization of the infection over time. Here we address the relevance of the study of cytopathic effect and describe different experimental alternatives for its application.